Pengaruh Kepemimpinan Transformasional dan Komitmen Organisasi terhadap Kinerja Karyawan melalui Kesiapan Berubah di Sekretariat Jenderal DPR RI - Khansa Dhia Savila; Jubery Marwan; Franky Franky (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of transformational leadership, organizational commitment, and readiness for change on employee performance, as well as to examine the indirect effects of transformational leadership and organizational commitment through readiness for change on cleaning service employees at the Secretariat General of the Indonesian House of Representatives (DPR RI). The background of this study arises from fluctuations in employee attendance and frequent management changes, accompanied by uncertainties related to employee transfers to the new capital city (IKN), which are suspected to affect work motivation and productivity. The study population consisted of 167 employees, and the sampling method employed was saturated sampling, making the entire population the research respondents. Data analysis was conducted using linear regression with the assistance of SPSS software to obtain accurate and systematic results. The findings indicate that transformational leadership, organizational commitment, and readiness for change significantly influence employee performance. Furthermore, readiness for change was proven to mediate the relationship between transformational leadership and organizational commitment and employee performance, thereby strengthening the role of employee readiness in responding effectively to organizational changes.